Tumor Suppressing Subtransferable Candidate 4 Expression Prevents Autophagy-Induced Cell Death Following Temozolomide Treatment in Glioblastoma Cells - Chen, Yongqiang; Gibson, Spencer B. (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GBM) is the most common and aggressive type of brain cancer in adults, with temozolomide (TMZ) being widely used as the standard chemotherapy drug for its treatment. However, GBM frequently becomes resistant to TMZ treatment due to various mechanisms including amplification and mutations of the epidermal growth factor receptor (EGFR), where EGFR variant III (EGFRvIII) is the most common EGFR mutation. Autophagy (macroautophagy) is an intracellular "self-degradation" process involving the lysosome. It mainly plays a pro-cell survival role contributing to drug resistance in cancers including GBM, but, under some conditions, it can induce cell death called autophagy-induced cell death (AuICD). We recently published that TSSC4 (tumor suppressing subtransferable candidate 4) is a novel tumor suppressor and a novel autophagy inhibitor that inhibits cancer cell growth through its interacting with the autophagy protein LC3. In this brief research report, we demonstrate that cell death induced by TMZ in GBM cells is inhibited by overexpression of TSSC4. TSSC4 overexpression also prevents TMZ-induced autophagy but not when TSSC4 is mutated in its conserved LC3-interacting region. When EGFRvIII was expressed in GBM cells, TSSC4 protein was increased and TMZ-induced cell death was decreased. Knockout of TSSC4 in EGFRvIII-expressing GBM cells increased TMZ-induced autophagy and cell death. This cell death was decreased by autophagy inhibition, suggesting that TSSC4 downregulation promotes TMZ-induced AuICD. This indicates that TSSC4 is a novel target to sensitize GBM cells to TMZ treatment.